2017
DOI: 10.1161/circimaging.116.005817
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Aortic Stiffness in Children With Pulmonary Arterial Hypertension

Abstract: Background Left ventricular (LV) dysfunction, mediated by ventricular interdependence, has been associated with negative outcomes in children with pulmonary arterial hypertension (PAH). Considering the dilation of the pulmonary arteries as a paramount sign of PAH, we hypothesized that the ascending aorta will present signs of apparent stiffness in children with PAH, and that this effect may be due to mechanical interaction with the dilated main pulmonary artery (MPA). Methods and Results 42 children with PAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Furthermore, tonometric studies do not take into account pulse wave reflections and bifurcation morphology, which can significantly alter PWV measurements . Reported PWV values for the ascending and descending aorta were in agreement with previously reported studies considering a flow‐area and wave‐propagation method . In this study, we found elevated PWV in ascending and descending aorta using a PC‐MRI‐derived technique, which is arguably the gold standard noninvasive technique for assessment of central aortic stiffness .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, tonometric studies do not take into account pulse wave reflections and bifurcation morphology, which can significantly alter PWV measurements . Reported PWV values for the ascending and descending aorta were in agreement with previously reported studies considering a flow‐area and wave‐propagation method . In this study, we found elevated PWV in ascending and descending aorta using a PC‐MRI‐derived technique, which is arguably the gold standard noninvasive technique for assessment of central aortic stiffness .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found elevated PWV in ascending and descending aorta using a PC‐MRI‐derived technique, which is arguably the gold standard noninvasive technique for assessment of central aortic stiffness . We specifically applied the flow‐area method, which can be reliably applied to investigate stiffness in discrete vascular segment when sufficient temporal resolution is guaranteed . Additional studies are required to explore the status of thoraco‐abdominal and abdominal aorta to better understand the extracardiac inflammatory processes in KD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations